Getting Back on Track : Reviving Growth and Securing Prosperity for All - World Bank Group (World Bank, Washington, DC, 2016)
Over the past few decades, Thailand has made tremendous progress toward the twin goals of eliminating extreme poverty and boosting shared prosperity. Thailand has achieved these gains despite high political instability. Growth has been slowing, and continued instability could affect future growth and prospects for shared income gains. Moreover, poverty and inequality continue to pose significant challenges. Slower growth than in the past, if it continues, will constrain further progress in reducing poverty and promoting inclusion. The key engines that drove past growth have lost steam or are unsustainable. Analysis undertaken for this SCD suggests that the significant slowdown in Thailand’s export growth in recent years is due in part to a loss of market share in labor-intensive manufacturing. Thailand has lost the competitive edge it once enjoyed over its peers and other countries in the region.